2002
DOI: 10.1007/s00122-002-0934-0
|View full text |Cite
|
Sign up to set email alerts
|

Identification of AFLP and microsatellite markers linked with an aluminium tolerance gene in barley (Hordeum vulgare L.)

Abstract: Barley is the most sensitive among the cereals to aluminium (Al) stress and breeding for more tolerant cultivars is a priority. To enhance selection efficiency for Al tolerance in barley, PCR-based AFLP and microsatellite markers linked to a locus conferring tolerance to aluminium were identified. The study used F(2) progeny derived from a single cross between Yambla (moderately tolerant of Al) and WB229 (tolerant of Al) and developed hydroponic pulse-recovery screening methods to assess tolerance of phenotype… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
58
0
2

Year Published

2003
2003
2012
2012

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 81 publications
(64 citation statements)
references
References 29 publications
4
58
0
2
Order By: Relevance
“…Nevertheless, the high root growth found in lines containing the 4H chromosome of barley, irrespective of the parents, indicated the presence of quantitative trait loci (QTL) for root elongation on chromosomes 4H. A similar association was found previously by Raman et al [19], Jefferies et al [28] and Ellis et al [29] under different stress conditions. When evaluating the Al tolerance level of these introgression lines and parental genotypes, similar results were found by monitoring root growth and by the haematoxylin test.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…Nevertheless, the high root growth found in lines containing the 4H chromosome of barley, irrespective of the parents, indicated the presence of quantitative trait loci (QTL) for root elongation on chromosomes 4H. A similar association was found previously by Raman et al [19], Jefferies et al [28] and Ellis et al [29] under different stress conditions. When evaluating the Al tolerance level of these introgression lines and parental genotypes, similar results were found by monitoring root growth and by the haematoxylin test.…”
Section: Discussionsupporting
confidence: 80%
“…They encode transport proteins responsible for malate and citrate release. Nevertheless, several minor QTLs controlling Al tolerance were also identified on chromosomes 2A, 5A, 3B and 5D in wheat and 2H, 3H, 5H and 6H in barley, indicating the multigenic trait of Al tolerance [19][20][21]. In addition, crosses between different genotypes or species have demonstrated that the presence of alien chromosomes may affect the Al tolerance of introgression lines.…”
Section: Introductionmentioning
confidence: 99%
“…All eight tolerant barley cultivars ranked by Minella and Sorrells (1992) were six-row cultivars. Two row barleys having Al tolerance have also been reported (Raman et al, 2002).…”
Section: Genotypic Difference In Al Tolerancementioning
confidence: 99%
“…Healthy leaf samples from these were used for validation of 4 microsatellite markers (EBmac0906, Bmac0310, Bmag0353, Bmac0181), which mapped within 10 cM of the locus conferring NFNB resistance in Sloop/ Halcyon. These markers have been reported to map closely in barley populations derived from Lina/Canada Park, WB229/Yambla, and Dayton/Harlan Hybrid (Ramsay et al 2000;Raman et al 2002Raman et al , 2003. Deoxyribonucleic acid was extracted in 2 mL Eppendorf tubes as described previously (Raman and Read 2000).…”
Section: Validation Of Microsatellite Markers Linked With Nfnb Resistmentioning
confidence: 99%